The Effect of the Discovery Learning Model Using PowerPoint Media on Students' Mathematical Critical Thinking Skills Regarding Systems of Linear Equations in Two Variables (SLPDV) - Romadona, Sahrul; Karo-karo, IsranRasyid (Desimal: Jurnal Matematika, 2026)
Mathematical critical thinking is increasingly recognized as a fundamental competency in mathematics education because it enables students to analyze information, evaluate solution strategies, and justify mathematical conclusions. Despite the growing adoption of inquiry-oriented learning, limited empirical evidence explains how commonly available classroom technology can effectively support the cognitive processes underlying Discovery Learning to improve students' mathematical critical thinking. This study investigated the effect of PowerPoint-assisted Discovery Learning on eighth-grade students’ mathematical critical thinking in Systems of Linear Equations in Two Variables. A quantitative quasi-experimental approach employing a nonequivalent control group design was conducted with 50 students, consisting of 25 students in the experimental group and 25 in the control group. Data were collected using a validated essay-based mathematical critical thinking test comprising nine valid items with excellent reliability (Cronbach’s α = .9669) and analyzed using descriptive statistics and an independent-samples t-test after normality and homogeneity assumptions were satisfied. Students in the experimental group significantly outperformed those in the control group (87.40 vs. 58.08), t(48)=16.1489, p<.001., and the difference was statistically significant, t (48) = 16.1489, p < .001. These findings demonstrate that PowerPoint functions as an instructional scaffold supporting exploration, verification, and mathematical reasoning within Discovery Learning. The study contributes empirical evidence that integrating structured visual scaffolding with inquiry-oriented pedagogy provides an accessible and effective approach for strengthening mathematical critical thinking in lower-secondary mathematics education.